The THE RELATIONSHIP BETWEEN PARENTING MOTIVATION AND FATHER INVOLVEMENT IN FATHERS WHO RUN HOME-BASED BUSINESSES IN BUKITTINGGI CITY: Hubungan Motivasi Pengasuhan dengan Father Involvement pada Ayah yang Memiliki Usaha di Rumah di Kota Bukittinggi - Syifa Ryanto; Zulian Fikry (Proram studi pendidikan Sejarah Fakultas Keguruan Dan Ilmu Pendidikan Universaitas PGRI Banyuwangi, 2026)
Father involvement is a critical factor in child development, yet understanding of what drives it remains limited, particularly in the context of informal work. The prevalence of home-based businesses creates a unique situation where the boundaries between work and family life are no longer clearly defined, this condition has the potential to alter how motivation influences father involvement. This study aims to examine the relationship between parenting motivation and father involvement among home-based business owners in Bukittinggi City, while considering the roles of internal and external motivation separately. The study employs a quantitative correlational approach with 97 respondents selected through purposive sampling. Data collection was conducted using the Inventory of Father Involvement (IFI) and a parenting motivation scale, followed by analysis using Pearson’s correlation test. The results indicate that father involvement was significantly correlated with both internal motivation (r = 0,745, p < 0.001) and external motivation (r = 0,827, p < 0,001), with both relationships being positive in direction. Based on the findings, external motivation showed a stronger correlation, indicating that when fathers are physically present at home, social pressures and expectations from the surrounding community become particularly relevant factors. These findings underscore the need for interventions aimed at increasing father involvement that target not only personal values but also support and expectations from the social environment, particularly for fathers with more flexible work arrangements.